A review of the contribution of livestock to food security, poverty alleviation and environmental sustainability in sub-Saharan Africa - Ehui, Simeon K. (Ethiopian Society of Animal Production, 2000)
This paper reviews the empirical evidence on the contribution of livestock to aggregate food supply, farm income, human nutrition, and to the environmental sustainability. It is divided in sections. The first section examines trends in livestock demand and supply and their projections to 2020. The second section presents the role of livestock as a source of income, food and nutrient supplies. The implications for poverty alleviation are derived from this section. The last section addresses the linkages between livestock and the environment.